Pengaruh Insight Media Sosial Instagram Terhadap Penjualan Produk Online - Handry Eldo (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
This research was created with the aim of finding out the influence of Instagram social media insights on online product sales on the Instagram social media platform.